2017
DOI: 10.2147/ppa.s127508
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adherence on subcutaneous interferon beta-1a effectiveness administered by Rebismart<sup>&reg;</sup> in patients with multiple sclerosis

Abstract: BackgroundAdherence to disease-modifying drugs (DMDs) is one of the key factors for achieving optimal clinical outcomes. Rebismart® is an injection device for subcutaneous administration of interferon beta-1a (INF β-1a) that is also able to monitor adherence objectively. The aim of this study was to describe adherence to INF β-1a using the said electronic autoinjection device and to explore the relationship between adherence and relapses in a Spanish cohort.MethodsThis is a retrospective observational study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Indeed, only seven patients in this study had an objective adherence below 80% and this did not allow us to reliably investigate associations with adherence measures inferior to this threshold. While we cannot exclude the possibility that other factors could be associated with low adherence to injections, we believe our data can provide useful information for neurologists and care givers in MS. Our findings are also in-line with more recent publications concerning adherence to injectables at the observational study level [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, only seven patients in this study had an objective adherence below 80% and this did not allow us to reliably investigate associations with adherence measures inferior to this threshold. While we cannot exclude the possibility that other factors could be associated with low adherence to injections, we believe our data can provide useful information for neurologists and care givers in MS. Our findings are also in-line with more recent publications concerning adherence to injectables at the observational study level [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…These real-life adherence data are consistent with findings from other recent trials, in which similarly high levels of objective adherence have been reported for patients using RebiSmart®. In a large study conducted at various sites across Europe (SMART), mean objective adherence among 912 patients with RRMS, over a 12-month study period, was 97.1% [ 10 ]; another retrospective study in Italy of 114 RRMS patients using RebiSmart® and followed up during a 1.536 ± 0.961 year period reported a mean objective adherence of 95.0 ± 9.0% [ 11 ]; while a more recent long-term retrospective study in Spain of 110 patients with MS, reported median adherence of 96.5% for a median period of 2.7 years [ 12 ]; and a smaller study in Finland reported 93.5% objective adherence for 29 patients with RRMS followed up over 24 weeks [ 13 ]. The long-term RIVER study showed median overall objective adherence of 85.2% for 57 patients over a mean 20.5 month observational period [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…High mean adherence rates ≥90% and high percentages of adherent patients at cutoffs of 80% and 90% have been reported in other recent long-term studies on MS DMTs. 6 , 7 , 13 , 30 35 In five studies, implementation was assessed by means of electronically recorded real-time administration data (RebiSmart ® ). 7 , 30 , 32 , 34 , 35 Two studies captured implementation on the basis of monthly self-reports, which is likely to have increased adherence by decreasing forgetfulness, the main reason for suboptimal implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to injectable DMTs and other interventional strategies is usually considered inferior in MS patients [10][11][12][13][14][15][16]; a retrospective study of MS patients initiating therapy with 1 of 4 injectable DMTs found that after 18 months, 11.2% of patients switched their medication, and 33.9% discontinued their treatment [17]. An adherence study on ambulatory patients carried out in Spain showed that after 2 years of starting DMT, INF-β was discontinued in 9.9% of patients, after 5 years discontinuation rose to 41.2% and after 8 years discontinuation rate was 58.7% [18].…”
Section: Plos Onementioning
confidence: 99%
“…Electronic auto-injection device (RebiSmart1; Merck Serono S.A.-Geneva, Switzerland, a branch of Merck Serono S.A., Coinsins, Switzerland, an affiliate of Merck KGaA, Darmstadt, Germany) was developed for the subcutaneous administration of IFN-β1a [10][11][12][13][14]20]. The device simplifies the injection process and help patients to overcome injection-related issues, thereby possibly increasing adherence to treatment.…”
Section: Plos Onementioning
confidence: 99%